Whole Genome Sequencing Provides an Added Value to the Investigation of Staphylococcal Food Poisoning Outbreaks - Nouws, Stéphanie; Bogaerts, Bert; Verhaegen, Bavo; Denayer, Sarah; Laeremans, Lasse; Marchal, Kathleen; Roosens, Nancy H. C.; Vanneste, Kevin; De Keersmaecker, Sigrid C. J. (Frontiers in Microbiology, 2021)
Through Staphylococcal enterotoxin (SE) production, Staphylococcus aureus is a common cause of food poisoning. Detection of staphylococcal food poisoning (SFP) is mostly performed using immunoassays, which however only detect five of 27 SEs described to date. Polymerase Chain Reactions are therefore frequently used in complement to identify a bigger arsenal of SE at gene level (se), but are labor-intensive. Complete se profiling of isolates from different sources, i.e. food and human cases, is, however, important to provide an indication on their potential link within foodborne outbreak investigation. In addition to complete se gene profiling, relatedness between isolates is determined with more certainty using pulsed-field gel electrophoresis, Staphylococcus protein A gene typing and other methods, but these have shown to lack resolution. We evaluated how Whole Genome Sequencing (WGS) can offer a solution to these shortcomings. By WGS analysis of a selection of S. aureus isolates, including some belonging to a confirmed foodborne outbreak, its added value as the ultimate multiplexing method was demonstrated. In contrast to PCR-based se gene detection for which primers sometimes showed to be non-specific, WGS enabled complete se gene profiling with high performance, provided that a database containing reference sequences for all se genes was constructed and employed. As an all-in-one approach with high resolution, WGS additionally allowed inferring correct isolate relationships. The different DNA extraction kits that we tested did affect neither se gene profiling, nor relatedness determination which is interesting for data sharing during SFP outbreak investigation. Although confirming the production of enterotoxins remains important for SFP investigation, we delivered a proof-of-concept that WGS is a valid alternative and/or complementary tool for outbreak investigation. An online user-friendly interface for se gene detection, using the custom-compiled database and parameters as described in this manuscript is available at https://galaxy.sciensano.be/tool_runner?tool_id=pipeline_staphylococcus.